Hadis Rasulullah Seputar Komunikasi Antarbudaya - Said Ahmad Sarhan Lubis (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
This paper intends to find out the hadiths about intercultural communication. Intercultural communication in essence can create harmony and togetherness. Besides that, they can also understand the differences between individuals. This also often happens in Indonesia, because Indonesia is a country that has a variety of cultures. And this difference must be supported, maintained and preserved. In addition, in essence, intercultural communication contains an intercultural dimension. In other words, the existence of intercultural communication has had a positive impact to make it easier to socialize and minimize misunderstandings. Communication is not only the knowledge learned in lecture classes. Even communication itself has actually been taught by the Creator, Allah SWT, through the Qur'an about how important communication is for humanity, especially Muslims. Lexically communication is the sending and receiving of messages or news between two or more people. So the message in question can be understood. Communication influences changes in behavior, ways of life, and values. Inter-cultural communication in an Islamic perspective is based on several emphases: 1. Religious: Habluminallah (Human-Allah relationship), 2. Social Value: Hablum Minannas (Human-Human Relations). So here Islam encourages its people so that religion does not always prioritize aspects of worship, but Islam also advocates social worship, such as paying attention to the fate of weak people.